How does gender impact economic evaluations in Brazil?: a multinomial logistic approach - Rosa, Isabel Seelaender Costa (2023)
Great effort has been devoted to the study of the gender gap in political science. Most of the presently available research has focused on gender as a dichotomous variable, disregarding within-gender differences. Although an area with considerably less development, burgeoning developments in research help to theorize about why the general concept of the gender gap might vary among different groups of women and how, in turn, these differences might be determinant for behavior and preference shaping processes. Moreover, while most research is concentrated in developed countries, many patterns observed in these contexts may not apply to developing scenarios, where inequalities and vulnerability are enhanced. I contribute to these efforts by employing Latinobarometer data to test a theory about the impact of gender on economic evaluations, considering the mediating effect of other relevant variables that determine differences among women in developing contexts. I employ multinomial logistic models with interactions in an effort to better understand the mediating role of labor market related variables on commonly observed gender effects.